Reduced mutual coupling multiband MIMO patch antenna with swastik type mushroom EBG - Maturi Thirupathi; Baranikunta Harikrishna (Institute of Advanced Engineering and Science, 2019)
This paper presents a reduced mutual coupling 1x2 rectangular patch antenna. The major disadvantage of the MIMO is mutual coupling. When two antennas are placed nearby mutual coupling occurs. When mutual coupling occurs decrease the channel capacity. Hence the propose system which resonates at first 2.5GHz, second is resonates at 5.4GHz. Two closely spaced antenna elements are separated by a distance of λmax/8. Here Swastik type mushroom EBG is introduced. EBG is placed between the two antennas. When EBG is placed between the two antennas good coupling reduction is obtained. This design is excellent isolation of -35dB and -25dB can be observed in the simulation results.